Intragastric pH and pressure profiles after intake of the high-caloric, high-fat meal as used for food effect studies - Koziolek, M.; Schneider, F.; Grimm, M.; Modeβ, Chr; Seekamp, A.; Roustom, T.; Siegmund, W.; Weitschies, W. (Journal of controlled release, 2015)
The intraluminal conditions of the fed stomach are critical for drug release from solid oral dosage forms and thus, often associated with the occurrence of food effects on oral bioavailability. In this study, intragastric pH and pressure profiles present after the ingestion of the high-caloric, high-fat (964kcal) FDA standard breakfast were investigated in 19 healthy human subjects by using the telemetric SmartPill® capsule system (26×13mm). Since the gastric emptying of such large non-digestible objects is typically accomplished by the migrating motor complex phase III activity, the time required for recurrence of fasted state motility determined the gastric emptying time (GET). Following the diet recommendations of the FDA guidance on food effect studies, the mean GET of the telemetric motility capsule was 15.3±4.7h. Thus, the high caloric value of the standard breakfast impeded gastric emptying before lunch in 18 out of 19 subjects. During its gastric transit, the capsule was exposed to highly dynamic conditions in terms of pH and pressure, which were mainly dependent on further meal and liquid intake, as well as the intragastric capsule deposition behavior. Maximum pH values in the stomach were measured immediately after capsule intake. The median pH value of the 5min period after capsule ingestion ranged between pH3.3 and 5.3. Subsequently, the pH decreased relatively constantly and reached minimum values of pH0–1 after approximately 4h. The maximum pressure within the stomach amounted to 293±109mbar and was clearly higher than the maximum pressure measured at the ileocaecal junction (60±35mbar). The physiological data on the intraluminal conditions within the fed stomach generated in this study will hopefully contribute to a better understanding of food effects on oral drug product performance. [Display omitted]